The Orange riots : Irish political violence in New York City, 1870 and 1871 - Gordon, Michael A. (Michael Allen), 1941- (Cornell University Press, 1993)
"In this book Michael A. Gordon examines the causes and consequences of the tragic and bloody "Orange Riots" that rocked New York City in 1870 and 1871. On July 12 of both years, groups of Irish Catholics clashed with Irish Protestants marching to commemorate the victory of 1690 at the Battle of the Boyne that confirmed the Protestant Ascendancy in Ireland. The violence of 1870 left eight people dead; a year later, more than sixty died." "Reconstructing the events of July 12 in those years, Gordon provides a riveting and richly detailed account of the riots. He maintains that they stemmed from more than religious hatred or generations of oppression in Ireland. Rather, both years bear witness to a struggle between two profoundly different visions of the promise of America: recreation of European social classes or a form of life liberated from the constraints and stratifications of the Old World. These visions were enmeshed in the turbulent ideological and political confrontations arising from industrialization and newly found immigrant power under New York City's notorious mayor, William Marcy "Boss" Tweed. Gordon concludes by showing how the riots sparked a reform movement that toppled Tweed from power and led to the restructuring of city politics in the 1870s." "Capturing the texture of Irish New York after the Civil War, this book is certain to receive the close attention of historians of immigration, of urban and working-class life, and of religion."--Jacket